Language education in social studies and science instruction: Ein Pilotprojekt in der Lehrer/-innenbildung der Privaten Pädagogischen Hochschule der Diözese Linz (Pedagogical Horizons, 2017)
Aiming at focusing on language education in social studies and science instruction in the course of studies (primary school) and ultimately in Austrian schools, a pilot study was conducted in summer term 2016 at the Private University of Education Diocese Linz. In this project, the subjects of german studies and  social studies/science instruction are brought together within the frame of language education in all subjects. We present first results of the pilot study, shed light on the transfer of theory into practise and exemplarily evaluate the process of the pilot project.